Cooking the Turkish way : culturally authentic foods including low-fat and vegetarian recipes - Cornell, Kari A. (Easy menu ethnic cookbooks., 2004)
An introduction to cooking in Turkey, featuring such recipes as spinach-filled Anatolian flat bread, lamb kebabs, and baklava. Also includes information on the history, geography, customs, and people of this partly European and partly Asian country.